Towards The Study of Cloud Computing and Its Security (International Journal of Engineering and Computer Science, 2017)
In the current trends of computing, cloud computing plays a vital role and it is emerging at the level of maximum. The reason behind this is people started moving their data to cloud with the expectation of hundred percentage availability on their demand, i.e., anytime anywhere computing. Though the cloud services are provided by the third party, security becomes a very big question mark. The main objective of this paper is to provide an overview of cloud computing and its security, which help the young researchers to get clear idea.